Frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17) - Wszolek, Zbigniew K (BioMed Central, 2006)
Frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17) is an autosomal dominant neurodegenerative disorder, which has three cardinal features: behavioral and personality changes, cognitive impairment, and motor symptoms. FTDP-17 was defined during the International Consensus Conference in Ann Arbor, Michigan, in 1996. The prevalence and incidence remain unknown but FTDP-17 is an extremely rare condition. It is caused by mutations in the tau gene, which encodes a microtubule-binding protein. Over 100 families with 38 different mutations in the tau gene have been identified worldwide. The phenotype of FTDP-17 varies not only between families carrying different mutations but also between and within families carrying the same mutations. The pathogenetic mechanisms underlying the disorder are thought to be related to the altered proportion of tau isoforms or to the ability of tau to bind microtubules and to promote microtubule assembly. Definitive diagnosis of FTDP-17 requires a combination of characteristic clinical and pathological features and molecular genetic analysis. Genetic counseling should be offered to affected and at-risk individuals; for most subtypes, penetrance is incomplete. Currently, treatment for FTDP-17 is only symptomatic and supportive. The prognosis and rate of the disease's progression vary considerably among individual patients and genetic kindreds, ranging from life expectancies of several months to several years, and, in exceptional cases, as long as two decades.